EFEKTIVITAS TABLET ZAT BESI TERHADAP PERUBAHAN TEKANAN DARAH IBU HAMIL - Damayanti .; Nia Surtika Gulo; Diah Evawanna Anuhgerah; Dwi Handayani (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2021)
Changes in blood pressure are normal during pregnancy. Because, the hormone progesterone which is produced during pregnancy, can relax the walls of blood vessels. Sagging walls of blood vessels, can reduce blood pressure in the first trimester and second trimester of pregnancy. This condition can cause dizziness when sitting or standing suddenly. Normal blood pressure values ​​in pregnant women do not differ from general conditions, which is 120/80 mmHg. If the blood pressure is recorded below 90/60 mmHg, this can indicate a blood pressure less. This research aims to To find out how the effectiveness of iron tablets on changes in blood pressure of pregnant women at Rosni Alizar Pratama Clinic, Medan Timur District, Deli Serdang Regency in 2020. This type of research is a quasi-experimental study with a Pretest-Posttest with control group approach. The study population was all pregnant women who did ANC examination at Rosni Alizar Pratama Clinic as many as 38 people. The sample selection using purposive sampling was calculated using the Slovin formula of 28 people. The results of the study used Wilcoxon test results obtained 0.157 and 1,000 > 0.05. It is expected that health workers on duty at the research site always measure vital signs for pregnant women during ANC visits. Conclusion : There is no effectiveness in giving iron tablets to changes in blood pressure in pregnant women Keywords: iron tablet, blood pressure, pregnant women